Análisis comparativo de la seguridad en aplicaciones de mensajería cifrada: evaluación de vulnerabilidades y amenazas en Whatsapp, Signal y Telegram. - Diaz Araujo, Luis Francisco (2025)
This study focuses on a comparative analysis of the security of encrypted messaging applications such as Whatsapp, Telegram and Signal, evaluating vulnerabilities and the threats they could suffer. Managing to evidence the poor security for known cyberattacks, such as phishing. Privacy is essential on the internet, this comparison reveals the permissions that messaging applications request from our devices, to be able to access functions that if we do not accept, we will not be able to make use of them.